Pengalaman Komunikasi Orang dengan HIV/AIDS (ODHA) di Kota Bekasi - Alfa Rizki Febriansyah; Fardiah Oktariani Lubis; Rastri Kusumaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the communication experiences of People Living with HIV/AIDS (PLHIV) in Bekasi City. Employing a qualitative phenomenological approach within the framework of Berger and Luckmann's Social Construction of Reality theory, the research involved seven PLHIV informants undergoing Antiretroviral (ARV) therapy. The findings indicate that PLHIV's communication experiences are highly varied, encompassing positive interactions from immediate family support, peer communities, and healthcare professionals, as well as negative experiences such as stigma and discrimination from the social environment. These communication experiences fundamentally shape the social reality and identity of PLHIV. This study emphasizes that communication, whether positive or negative, plays a crucial role in forming PLHIV's self-perception and social interactions, and highlights the importance of empathetic communication support to reduce stigma and improve their quality of life.